Quantification of Platelet-associated IgG for Differential Diagnosis of Patients with Thrombocytopenia - Hagenström, H.; Schlenke, P.; Hennig, H.; Kirchner, H.; Klüter, H. (Thrombosis and Haemostasis, 2000)
Immune thrombocytopenia is due to platelet destruction by circulating glycoprotein-specific antibodies and is found in various disorders. Methods for the detection of platelet-associated IgG (PAIgG) are generally sensitive but unspecific, whereas glycoprotein-specific assays are highly specific but less sensitive. Usefully, a sensitive screening method for PAIgG detection would also provide information for differential diagnosis. We developed a quantitative direct Platelet Immunofluorescence Test (PIFT) by flow cytometry and studied 79 thrombocytopenic patients with immune thrombocytopenia and other disorders. The sensitivity of the assay was 94%, its specificity 66% for the detection of a clinically obvious immune thrombocytopenia. PAIgG levels of patients with immune thrombocytopenia differed significantly from those of other patients with low platelet counts (p <0.001). The quantitative PIFT proved to be a sensitive method for PAIgG detection and should therefore be used as a screening method. In addition, it could be helpful for differential diagnosis in marked thrombocytopenia where a MAIPA is not feasible.
Keywords: Thrombocytopenia; platelet-associated IgG; flow cytometry